Factors Affecting Budget Changes: Setting Planning, Leadership Style and Government Policy - Cris Kuntadi; Rita Tri Damayantie (Journal Research of Social Science, Economics, and Management, 2022)
Changes that occur in a budget are driven by several factors, which can arise from both internal and external to an organization. This article examines the factors that influence budget changes, namely: setting planning, leadership styles and government policies. It is hoped that this article can contribute ideas to build hypotheses of influence between variables to be used in future research. The results of this literature review article are: 1) the determination of planning affects budget changes; 2) leadership style affects budget changes; and 3) government policies affect budget changes. Each of the factors discussed in this article has a positive influence on the decision of an organization to make a budget change.